From Leipzig to Leipzig. Territorial Research Delivers Evidence for the New Territorial Agenda of the European Union. - Böhme, Kai; Schön, Peter (TH Zürich, NSL, 2006)
Auf der Grundlage der Leipziger Grundsätze (1994) soll auf der kommenden Sitzung der für Raumplanung zuständigen EU-Minister (2007) ebenfalls in Leipzig die Territoriale Agenda der Europäischen Union verabschiedet werden. Der Beitrag analysiert den Weg von "Leipzig nach Leipzig". Dabei wird ein deutlicher Trend der Institutionalisierung der raumbezogenen Forschung in Europa deutlich, von einem losen Netzwerk von Forschungseinrichtungen hin zu der neu eingerichteten Institution ESPON. Auf der politischen Ebene stellt sich die Entwicklung ambivalent dar: der Prozess der weiteren Institutionalisierung, wie er von der ESDP begonnen wurde, wurde abgebrochen, andererseits verlangt die Europäische Verfassung von der Politik eine Stärkung der territorialen Kohäsion. Da aber wiederum der Verfassungsprozess gestoppt ist, stellt sich das Zusammenspiel von Forschung und Fachpolitik als ein gegenläufiges Miteinander von Insitutionalisierung und De-Instituionalisierung dar. goj/difu

For more than ten years now, EU Member States and the European Commission have been cooperating to agree on joint views and strategies for a European Spatial Development Policy. Based on the "Leipzig Principles", adopted in Leipzig in 1994, it is now planned to agree on a Territorial Agenda, at the next ministerial meeting in Leipzig, May 2007. In this article, we will analyze the road "from Leipzig to Leipzig". We will focus on the interplay between policy and science, or evidence, which together form the results in this process. A major result of our investigations is that "institutionalization matters". We can see a clear trend to a stronger institutionalized base on the research side, from loose networks of national institutes to a newly created institution, ESPON, which was formed as a network with its own managing structure. The development in the policy-arena is more ambivalent. After the adoption of the ESDP in 1999, its institutional base that took care of intergovernmental spatial policies at the European level was dismantled, and the present structure to prepare the Territorial Agenda is much weaker. On the other hand, the EU Constitution proposes a stronger legal and institutional base for "territorial cohesion" policies, but, as is well known, the ratification process has been stalled. Actually, the interplay of policy and evidence is situated in an ambiguous setting of diverse processes of institutionalization and de-institutionalization. difu
Keywords: Raumordnung; Raumplanung; Raumforschung; Planungstheorie; Raumordnungspolitik; Planungspraxis; Raumentwicklungspolitik; Planungsgeschichte; Kohäsionspolitik; Planungswissenschaft